Pengaruh Kapasitas Olah, Ketersediaan Bahan Baku dan Capaian Rendemen Terhadap Harga Pokok Pengolahan Pabrik Kelapa Sawit di Pabrik Kelapa Sawit Torgamba PT. Perkebunan Nusantara III (Persero) - Atmaja, Yuda Pratama; Akoeb, Erwin Nyak; Siregar, M. Akbar (Universitas Medan Area, 2020)
Palm oil was first introduced in Indonesia by the Dutch government in 1848, at that time there were 4 oil palm seedlings planted at Bogor Botanical Garden (Botanical Garden) in Bogor, two from Bourbon (Mauritius) and two from the Hortus Botanicus, Amsterdam ( Netherlands). Currently the development of oil palm cultivation is increasing with an area of 2017 covering 11.5 million hectares and the production of palm oil (CPO) has reached Â± 30 million tons in 2018. The main objective of this research is to find out the influence of the increase of capacity achievement, availability of raw materials and the achievement of oil and palm kernel oil to the performance of oil palm factory, especially the cost of processing so that it can give added value to the company. Based on the result of the research, it is known that the capacity of X1 is negative but not significant. This is in accordance with the hypothesis, the availability of raw material (X2) is negative but not significant and the yield of rendement (X3) is negative but not significant this is in accordance with the hypothesis and capacity though, the availability of raw materials and yields of yields together have a significant effect on the cost of processing. On the basis of this, then the management should increase attention to the capacity of the process, the availability of raw materials and the achievement of rendemen to minimize the basic price.